Antistreptococcal, neuronal, and nuclear antibodies in Tourette syndrome - Loiselle, Christopher R; Wendlandt, John T; Rohde, Charles A; Singer, Harvey S (Pediatric neurology, 2003)
Previous studies have suggested associations between Tourette syndrome and attention-deficit–hyperactivity disorder and antistreptococcal antibodies and between Tourette syndrome and antinuclear antibodies. In this study, antistreptolysin O, antideoxyribonuclease B, antinuclear, and antineuronal antibodies were measured in 41 children with Tourette syndrome and 38 controls, selected without regard to history of streptococcal infection. Results revealed that mean antistreptococcal titers did not differ between diagnostic groups. In addition, multiple regression analysis was unable to predict antistreptococcal antibody titers according to age and diagnosis. The frequency of elevated antistreptolysin O titers, based on a cutoff of 1:240, was significantly higher ( P = 0.04) in patients with attention-deficit–hyperactivity disorder (64%) than in the group without attention-deficit–hyperactivity disorder (34%) but not when dichotomized according to age-matched normal values. No analysis of antideoxyribonuclease B titers identified any differences between groups. Antinuclear antibody titers were at least 1:160 in three of 33 Tourette syndrome patients; only one subject manifested a homogeneous staining pattern. Multiple regression analyses were unable to predict antinuclear, antineuronal, or anti-HTB-10 antibody titers according to the combination of age, diagnosis, and antistreptococcal titer. We suggest that longitudinal rather than single-point-in-time laboratory measurements be evaluated before definitive conclusions are drawn on associations between the diagnosis of Tourette syndrome, attention-deficit–hyperactivity disorder, or obsessive-compulsive disorders and antistreptococcal or antinuclear antibody titers.